Efeitos da fotobiomodulação utilizando LED associado ao exercício físico sobre os aspectos morfológicos musculares e reparo do tecido nervoso pós lesão por esmagamento de nervo ciático em ratos Wistar - Soldera, Carla Bernardo (2020)
Contextualization: Traumatic injuries of the peripheral nervous system are common today, being an important medical problem. The aim of the present study was to evaluate the effects of immediate exercise associated with photobiomodulation therapy using LED as a rehabilitation after peripheral nerve injury by crushing the sciatic nerve in Wistar rats. Methodology: 45 Wistar rats were used, randomly divided into 5 groups: Control; Injury; Injury+LEDn+Exercise; Injury+LEDnm+Exercise; Injury+Exercise. The animals were euthanized 7 and 14 days after the operation. Photobiomodulation therapy consisted of the use of 850nm LED, 1cm2 beam area (nerve region total of 4 points, energy per point 0.8J, time per point of 20sec, total energy 3.2J and muscle region total of 8 points, energy per point 0.4J, time per point 10sec, total energy 3.2J), in a punctual way in contact with the animal's skin, with daily applications for 5 consecutive days, starting 2h after the crush injury. For exercise training, a treadmill adapted for training with rats containing lanes and digital speed control was used. The exercise protocol consisted of daily training started 24 hours after the operation, being performed 30 minutes/day, five days a week, without inclination. After each experimental period, functional analysis of gait was performed using the functional sciatic index, analysis of mechanical hyperalgesia using the Von Frey test, analysis of muscle mass to assess muscle atrophy, qualitative and quantitative assessment of muscle morphological aspects and qualitative analysis and quantitative of collagen fibers. Results: Regarding gait assessment, all injured groups showed a worsening in the functional index assessed after 7 and 14 days of injury, and it was observed in 7 days that the Injury+LEDn+Exercise group performed better when compared to the others. injured and treated groups. In 14 days, the Injury+LEDn+Exercise group performed better when compared to the Injury group. Regarding the analysis of muscle mass, after 7 days, all injured groups, treated or not, showed a decrease in the muscle mass ratio indicating an increase in atrophy when compared to the Control group, and the same occurred in 14 days. The Injury+LEDn+Exercise group in 14 days showed an improvement when compared to the Lesion group indicating less muscle atrophy. Regarding hyperalgesia, in the period of 7 and 14 days all injured groups, treated or not, showed a decrease in nociception in relation to the Control group. In 14 days, the Injury+LEDn+Exercise and Injury+LEDnm+Exercise groups showed better results when compared to the Injury group. It was also shown that in the same period that the injured and treated groups with LED both in the nerve region and in the nerve and muscle associated with exercise showed better results when compared to the Injury+Exercise group only. Conclusion: Based on the results, it was possible to conclude that the use of photobiomodulation when applied to the nervous region associated with early-onset exercise can contribute to a functional improvement in gait, reduces muscle atrophy and acts positively on nociception.